ACCURACY OF GLUCOSE CHALLENGE TEST IN SCREENING OF GESTATIONAL DIABTES MELLITUS - Anees Fatima; Quddsia Tanveer; Mubashra Naz et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: To determine the diagnostic accuracy of glucose challenge test for diagnosis of gestational diabetes by taking glucose tolerance test as gold standard.PATIENTS AND METHOD: It was a cross-sectional validation study. Duration of study was 6 months from June 2010 to December 2010. The study was conducted in OB/GYN unit-I, Allied hospital, Faisalabad. 267 pregnant women were included in the study after explaining the risks and beneﬁts. Glucose challenge test (GCT) and a Glucose tolerance test (GTT) both were carried out on all patients. GTT was taken as the Gold standard test and results of the glucose challenge test were compared with the result of GTT. Main outcome measures were Sensitivity, speciﬁcity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of glucose challenge test.RESULTS: Out of 267 patients, 74 patients were true positive and 167 patients were true negative as diagnosed by GCT. GCT failed to diagnose 16 diabetics (false negative) and wrongly diagnosed diabetes mellitus (false positive) in 10 normal participants as conﬁrmed by use of the gold standard. The sensitivity of GCT was 82%, speciﬁcity was 94%, PPV was 88%, NPV was 91.25 and accuracy of GCT as a screening test for GDM was 90%.CONCLUSION: In our population, with the high prevalence of GDM, glucose challenge test is found to be an acceptable and useful screening test for GDM.